PENGARUH KESEMPATAN INVESTASI (IOS), KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2011-2014) - M. Fattah Arrasyid, 11.05.52.0156; Suwarti, Titiek (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of investment opportunities (IOS), dividend policy, firm size, leverage and profitability of the enterprise value of the banking company listed on the Indonesia Stock Exchange period 2011-2014.Â Population of this research is the overall banking companies listed in Indonesia Stock Exchange during the period of 2011 through 2014. The procedure used to determine the sample is purposive sampling method sampling technique with a certain consideration. According to predetermined criteria there are 44 observation data. The analysis technique used is multiple linear regression.Â Based on the test results it can be concluded that the investment opportunity positive effect on firm value. Dividend policy does not affect the value of the company. The size of the company and significant positive effect on firm value. Leverage a positive effect on firm value. Profitability has no effect on the value of the company.Keywords: Investment Opportunity, Dividend Policy, Firm Size, Leverage, Profitability And Corporate Value